PENGARUH LINGKUNGAN KERJA, KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. INDOSPRING TBK GRESIK - Bagus Priambodo; Waras Waras (Jurnal Ekonomi, Bisnis dan Social, 2024)
The study aims to examine and analyze the effect of work environment, compensation and work motivation on employee performance at PT. Indsopring Tbk Gresik. The unit analysis in study was 67 PT. Indospring TBK shearing devition employee. Sampling technique using the sensus sample. Data analysis was performed using statistic with SPSS tools. Based on the results of data analysis using the t test it is known that partially work environment not have a significant effect. And simultaneous work environment, compensation and work motivation have a significant effect.